Apparatus Competency Gap in SPBE Services: An Analysis of Public Administration Literature - Abdi Susanto; Amirul Mustofa; Sedarmayanti Sedarmayanti; Dian Ferriswara (International Journal of Humanities and Social Sciences Reviews, 2026)
The implementation of Electronic-Based Government Systems (Sistem Pemerintahan Berbasis Elektronik/SPBE) represents a strategic instrument of public administration reform aimed at improving service quality, efficiency, and governance through digital transformation. However, empirical evidence across countries indicates that the effectiveness of digital government initiatives is frequently constrained by persistent competency gaps among public sector personnel. This study conducts a thematic literature review to systematically identify, classify, and synthesize scholarly findings on competency gaps affecting SPBE and digital government implementation within the field of public administration. Drawing on peer-reviewed international literature published over the last decade and indexed in Scopus, Web of Science, and DOAJ, the review applies a narrative–synthetic approach supported by thematic analysis. The findings reveal four dominant dimensions of competency gaps: technical–digital competencies, managerial and digital leadership competencies, cross-sectoral collaborative competencies, and adaptive learning competencies. These gaps are shaped by interacting individual, organizational, and systemic factors, including misaligned human resource management practices, fragmented bureaucratic structures, and limited capacity-building mechanisms. Using Competency-Based Human Resource Management (CBHRM) as the primary analytical lens, and reinforced by Digital Government Theory, Digital Era Governance, and Capacity Building Theory, this study demonstrates that competency gaps are structural rather than merely individual deficiencies. The article contributes theoretically by integrating human resource and digital governance perspectives into a unified analytical framework, and practically by offering policy-relevant insights for strengthening public sector capacity and enhancing the sustainability of SPBE implementation.